دور عصرنة الخدمة العمومية في تحسين أداء المورد البشري بقطاع الجماعات المحلية (Journal of Economics and Management Research, 2020)
هدفت الدراسة إلى دراسة دور عصرنة الجماعات المحلية في تحسين أداء المورد حيث تم استخدام المنهج الوصفي، كما تم الاعتماد على دراسة الحالة من خلال الملاحظة والوثائق الرسمية، والاستبيان ومعالجته الإحصائية عن طريق برنامج spss نسخة 22 .وتمت الدراسة على عينة من موظفي بلديات دائرة سيدي خويلد والمتمثلة في 56 موظف تم اختيارها بطريقة قصدية. وتوصلت الدراسة الى بوجود علاقة تأثير مباشر ذات دلالة إحصائية بين عصرنة الجماعات المحلية، وانعكاس ذلك على أداء المورد البشري عند مستوى دلالة (0.01) ببلديات دائرة سيدي خويلد. Abstract: The study aimed to study the role of modernizing local groups in improving the performance of the resource, as the descriptive approach was used, and the case study was relied on through observation and official documents, and the questionnaire and its statistical treatment through the spss program version 22. And represented in 56 employees chosen in a deliberate way. The study concluded that there is a direct, statistically significant impact relationship between modernization of local communities, and its reflection on the performance of the human resource at a significance level (0.01) in the municipalities of Sidi Khwailed district.